WNT1-inducible signaling protein–1 mediates pulmonary fibrosis in mice and is upregulated in humans with idiopathic pulmonary fibrosis - Königshoff, Melanie; Kramer, Monika; Balsara, Nisha; Wilhelm, Jochen; Amarie, Oana Veronica; Jahn, Andreas; Rose, Frank; Fink, Ludger; Seeger, Werner; Schaefer, Liliana; Günther, Andreas; Eickelberg, Oliver (The Journal of clinical investigation, 2009)
Idiopathic pulmonary fibrosis (IPF) is characterized by distorted lung architecture and loss of respiratory function. Enhanced (myo)fibroblast activation, ECM deposition, and alveolar epithelial type II (ATII) cell dysfunction contribute to IPF pathogenesis. However, the molecular pathways linking ATII cell dysfunction with the development of fibrosis are poorly understood. Here, we demonstrate, in a mouse model of pulmonary fibrosis, increased proliferation and altered expression of components of the WNT/beta-catenin signaling pathway in ATII cells. Further analysis revealed that expression of WNT1-inducible signaling protein-1 (WISP1), which is encoded by a WNT target gene, was increased in ATII cells in both a mouse model of pulmonary fibrosis and patients with IPF. Treatment of mouse primary ATII cells with recombinant WISP1 led to increased proliferation and epithelial-mesenchymal transition (EMT), while treatment of mouse and human lung fibroblasts with recombinant WISP1 enhanced deposition of ECM components. In the mouse model of pulmonary fibrosis, neutralizing mAbs specific for WISP1 reduced the expression of genes characteristic of fibrosis and reversed the expression of genes associated with EMT. More importantly, these changes in gene expression were associated with marked attenuation of lung fibrosis, including decreased collagen deposition and improved lung function and survival. Our study thus identifies WISP1 as a key regulator of ATII cell hyperplasia and plasticity as well as a potential therapeutic target for attenuation of pulmonary fibrosis.